2022
DOI: 10.1027/0227-5910/a000788
|View full text |Cite
|
Sign up to set email alerts
|

Iran's National Suicide Prevention Program

Abstract: Abstract. Background and Aims: Iran is one of the few countries in the Eastern Mediterranean Region (EMR) to have developed a national suicide prevention program (NSPP). This report introduces Iran's NSPP to policy planners and researchers working in suicide prevention, and is intended to encourage other low- and middle-income countries to develop, implement, and evaluate their own NSPPs. Method: This was a case study of a NSPP in one country, integrating quantitative and qualitative data. Bibliographic search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The nationwide report further showed that the current suicide rate increased by 31 times between 1991 and 2011; such an increase was the highest in suicide-related deaths among the eastern Mediterranean region and among Islamic countries. To counter this, Iran’s national suicide prevention program (NSPP) was established in 2010 [ 49 ]. The interim report from 2021 [ 49 ] concluded that, contrary to previous data [ 47 ], the national incidence of suicide appeared to be low, with higher incidence rates among young adults, females, and in western regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nationwide report further showed that the current suicide rate increased by 31 times between 1991 and 2011; such an increase was the highest in suicide-related deaths among the eastern Mediterranean region and among Islamic countries. To counter this, Iran’s national suicide prevention program (NSPP) was established in 2010 [ 49 ]. The interim report from 2021 [ 49 ] concluded that, contrary to previous data [ 47 ], the national incidence of suicide appeared to be low, with higher incidence rates among young adults, females, and in western regions.…”
Section: Introductionmentioning
confidence: 99%
“…To counter this, Iran’s national suicide prevention program (NSPP) was established in 2010 [ 49 ]. The interim report from 2021 [ 49 ] concluded that, contrary to previous data [ 47 ], the national incidence of suicide appeared to be low, with higher incidence rates among young adults, females, and in western regions. With this background in mind, it appeared reasonable to further investigate possible psychological factors to explain suicide attempts among Iranians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation